Disaster Preparedness from House for Earthquake-Prone Area in Sukabumi Area, West Java - Yunida Sofiana; Nabilla Retnaning; Siti Chadijah (Social Economics and Ecology International Journal (SEEIJ), 2022)
Indonesian territory is located in a region that is prone to earthquake disasters. Therefore, there is a need to educate the community about emergency scenarios related to earthquake disasters since they can happen at any time. One of the preventive measures that can be taken is how the community can arrange the interior of the house so that the house is safer and prevent the furniture from endangering the occupants of the house in the event of a disaster, especially an earthquake. This community service's goal is to foster community interaction through the creation of a furniture arrangement workshop inside the home to decrease risk. The strategy is implemented through a session on home organization. The strategy used takes the form of a workshop on how to set up homes safely. From the results of the workshop, it is envisaged that the community would be better able to comprehend how to arrange furniture in the home to prevent accidents. Workshops are provided in the form of pictures and tutorials along with examples of before and after arrangements to help the community better understand the layout of furniture that is under safety.